University students’ perceptions of the inner cities of Murcia and Valencia - Yago, Francisco José Morales; Lázaro y Torres, María Luisa de; Gomez Ruiz, María Luisa (Quaestiones Geographicae, 2018)
Inner city perceptions create a mental representation from different approaches: a visual approach, carried out through observation and description; a second approach, focused on evaluation and analysis of a city; and a third approach, which integrates the feelings that a space evokes in individuals known as the sense of the place. In the final analysis the aforementioned approach condition the behaviour (action-decision) of individuals. Image capture mainly happens while people walk in, travel to or visit a city using different ways to get around and they organize a mental map of the city. University students were selected from two Spanish cities: Murcia (215 respondents) and Valencia (300 respondents) to reply to a survey and to draw a map of their city. Results of the images of the cities in which they were currently living also proved useful in providing guidelines on sustainable growth of cities and in detecting deficiencies in order to correct them. The research model could be used in other cities throughout the world.